ANALISIS MAQASHID SYARI’AH TENTANG PRAKTIK JUAL BELI HASIL PERTANIAN PT (PERORANGAN) ABQORI EDU AGRARIAN - Misfaroh, Izza; Rosi, Fathor (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine the agricultural trade practices of PT (Individual Entity) Abqori Edu Agrarian through the theoretical lens of Maqashid Syari’ah, with a particular emphasis on the protection of wealth (ḥifẓ al-māl), preservation of life (ḥifẓ an-nafs), and social justice. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation of local agribusiness activities. The findings reveal that the company’s trading mechanism prioritizes transparency, fair pricing, and long-term partnerships between farmers and the management. These practices largely align with the objectives of Maqashid Syari’ah, especially in ensuring economic sustainability for farmers and promoting more equitable distribution of profits. Nevertheless, the study also identifies several practical challenges, such as limited grassroots literacy in Islamic economics, market asymmetries, and economic pressures from intermediaries (tengkulak), which collectively hinder the consistent application of Sharia principles. The research recommends enhanced Islamic economic education for micro-agribusiness stakeholders and more structural policy interventions to support ethical Sharia-based economic practices within the agricultural sector.